1983
DOI: 10.1007/bf00001055
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and development of the South American freshwater stingrays,Potamotrygon circularis and P. motoro

Abstract: SynopsisObservations of reproductive features and body measurements were made on wild-caught, freshwater stingrays, Potamotrygon circularis and P. motoro, from the Amazon drainage of western Brazil and southern Colombia. Further observations were made in Detroit's Belle Isle Aquarium on a captive pair of P. motoro and their descendants, which constitute the first known captive breeding colony of potamotrygonids. The gross structure and function of female and male reproductive systems are described. There is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 18 publications
3
38
1
4
Order By: Relevance
“…Neotropical freshwater stingrays have been considered completely adapted to freshwater environments because they have the ability to osmoregulate and reproduce in such habitats (Thorson et al, 1983). Most Amazonian river basins present a well-defined hydrologic cycle (Goulding, 1980;1997) and by inhabiting these water systems it is very probable that the freshwater stingrays had to adapt their life cycles to these cyclic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neotropical freshwater stingrays have been considered completely adapted to freshwater environments because they have the ability to osmoregulate and reproduce in such habitats (Thorson et al, 1983). Most Amazonian river basins present a well-defined hydrologic cycle (Goulding, 1980;1997) and by inhabiting these water systems it is very probable that the freshwater stingrays had to adapt their life cycles to these cyclic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The terminology used in the analyses was adapted from Dodd (1983) and observations were made according to Wourms et al (1988), Thorson et al (1983), Peres and Vooren (1991), Araújo (1998) and Charvet-Almeida (2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 25 stingrays were captured, being 15 P. motoro and 10 P. falkneri. Potamotrygon motoro specimens presented a total length between 257 and 457 mm, disk length between 168 and 265 mm, and weight between 380 and 980 g. Potamotrygon falkneri specimens presented 531 to 835 mm of total length, 254 to 445 mm of disk length, and a weight of 940 to 6550 g. Although the sampled specimens of P. motoro were smaller than the other species, Thorson et al (1983) reported that this species reaches a maximum length of 600 mm and 8.5 kg of weight. Although the literature about P. falkneri is scarce, a maximum length of 892 mm was cited for this species (Britski et al 1999).…”
Section: Resultsmentioning
confidence: 85%
“…The ingestion of fishes of the family Loricariidae was also reported by this author. For P. motoro, it seems that the majority of captured individuals were juveniles, with the sampled individuals having 1/3 and 1/8 of the size and weight, respectively, of the largest individuals reported in the literature (data from Thorson et al 1983). In addition, according to Achenbach & Achenbach (1976), reproductively mature individuals of P. motoro present disk sizes between 300 and 350 mm, larger than the disk sizes presented by the individuals collected in this study.…”
Section: Resultsmentioning
confidence: 89%